Crouzon syndrome: a case report - Singh, Gursharn; Malik, Supriya; Kaur, Jaskeen (International Journal of Contemporary Pediatrics, 2017)
Crouzon syndrome is an example of syndromes caused by premature obliteration and ossification of two or more sutures, most commonly coronal and sagittal. Described by a French neurosurgeon in 1912, it is a rare genetic disorder. Crouzon syndrome is caused by mutation in the Fibroblast Growth Factor Receptor 2 (FGFR2) gene. This disorder is characterized by distinctive malformations of skull and face (craniofacial region). Premature cranial suture closure is the most common skull abnormality. The case of an 8-month-old boy with Crouzon syndrome which is one of syndromes associated with synostosis, is presented. He presented in OPD with a cranial deformity, maxillary hypoplasia and exophthalmos. The clinical, characteristic radiological features and investigations carried out, along with treatment of this patient are discussed as part of multidisciplinary management.